GNSS/NTRIP SERVICE AND TECHNIQUE: ACCURACY TESTS - CINTRA, JORGE PIMENTEL; NERO, MARCELO ANTONIO; RODRIGUES, DANILO (Boletim de Ciências Geodésicas, 2011)
Experiments conducted at the School of Engineering of the University of São Paulo, Brazil, using GNSS/NTRIP technology are described and analyzed in terms of accuracy. The method consists in using the data of a reference station, the IBGE RBMC-IP stations, collected in a remote station, by means of the Internet and a mobile phone, to obtain more accurate real time coordinates than those of the navigation method. The experiments consist in surveying the known coordinate points and of the error analysis (accuracy). Firstly with short distances (in the USP Base for Equipment Calibration), and then over increasing distances up to about 30 km, in terms of the limits foreseen for the RTK method, and for other greater distances by using the DGPS method, up to 2,700 km. The following were tested and analyzed: the use of different reference stations, the variation in accuracy over distance, the use of a L1 receiver and a L1/L2 one, as well as the use of the RTK and DGPS techniques, in terms of accuracy reached, that is, the difference between these coordinates and others considered as standard, besides checking if the equipment reaches or not the accuracy stated in the manual.